The Quantum Theory of Atoms in Molecules 2007
DOI: 10.1002/9783527610709.ch16
|View full text |Cite
|
Sign up to set email alerts
|

Topological Properties of the Electron Distribution in Hydrogen‐bonded Systems

Abstract: The hydrogen bond (HB) is the most important weak interaction found in nature. It is responsible for the three dimensional shape of biopolymers (proteins and nucleic acids) and for the structure of water, in both the liquid and solid phases. Life processes extensively use the making and breaking of HBs as part of concatenated reactions involving huge amounts of biomolecules. In addition, it has profound implications in the mode of action of drugs and in molecular packing, recognition, and crystal engineering [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 35 publications
5
33
0
Order By: Relevance
“…However, previous reports have shown that this correlation should be exponential when larger ranges of distances are considered [45,46].…”
Section: Trimersmentioning
confidence: 81%
“…However, previous reports have shown that this correlation should be exponential when larger ranges of distances are considered [45,46].…”
Section: Trimersmentioning
confidence: 81%
“…This behavior differs from the tendencies observed in the studies of HB complexes (which showed negative ∇ 2 ρ values, with the magnitudes increasing exponentially with the decreasing the bond length in the covalent-bond region 18 ) However, similar positive or small negative Laplacian values were found earlier for the other covalent bonds formed by the highly polar atoms, which suggests that the Laplacian values of BCPs are not always a reliable indicator to allow an accurate covalent or noncovalent bond type assignment. 43 Therefore, the local energy density H ( r ) was proposed to complete the identification of the interatomic interactions. 43 Positive and negative values of H ( r ) have been used as an alternative way of defining ionic and covalent bonds because this quantity avoids the problems observed for ∇ 2 ρ( r ) with some covalent bonds.…”
Section: Results and Discussionmentioning
confidence: 99%
“…It is also noted that the calculated energies for the LP 2 (F)!s*OH interactions (close to 1 kcal mol -1 ) are too small to characterize it as a hydrogen bond. In the current literature [6,21,22] , it is accepted that the QTAIM method is more reliable than the NBO [17] approach to characterize hydrogen bonds. Ruling out the existence of a hydrogen bond for defining the preferential conformations for compounds 1 and 2, it is interesting to analyze how the 4 J FH SSCC involving the hydroxyl proton is transmitted.…”
Section: Resultsmentioning
confidence: 99%